2017
DOI: 10.1159/000453318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Macular Ganglion Cell-Inner Plexiform Layer and the Circumpapillary Retinal Nerve Fiber Layer in Early to Severe Stages of Glaucoma: Correlation with Central Visual Function and Visual Field Indexes

Abstract: Objectives: To compare the circumpapillary retinal nerve fiber layer (cpRNFL) and the macular ganglion cell-inner plexiform layer (GCIPL) in glaucoma patients at different disease stages and to evaluate correlations between optical coherence tomography (OCT) parameters with central visual function and visual field (VF) indexes. Patients and Methods: One hundred forty patients were included in this prospective cross-sectional study. Subjects diagnosed with chronic open-angle glaucoma and 20/40 or better vision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
6
15
0
1
Order By: Relevance
“…Lee et al [46] evaluated the rates of structural and functional changes among 465 eyes of 338 subjects with different severities of glaucoma and demonstrated that the VFI rates were significantly worse in the more advanced groups ( p < 0.001). Our results are in agreement with the conclusion of Bambo et al [52] that the correlations of central vision (the 4 central VF thresholds) and the VFI on the HFA 24-2 VF test with mGCIPLT were moderate and statistically significant in early-to-severe stages of glaucoma.…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al [46] evaluated the rates of structural and functional changes among 465 eyes of 338 subjects with different severities of glaucoma and demonstrated that the VFI rates were significantly worse in the more advanced groups ( p < 0.001). Our results are in agreement with the conclusion of Bambo et al [52] that the correlations of central vision (the 4 central VF thresholds) and the VFI on the HFA 24-2 VF test with mGCIPLT were moderate and statistically significant in early-to-severe stages of glaucoma.…”
Section: Discussionsupporting
confidence: 93%
“…To identify factors associated with the rate of MD progression, linear regression analysis was adopted using MD slope as the dependent variable ( Table 3 ). Since OCT parameters have been known for their robust associations with VF indices [ 22 , 23 , 24 ], we created two multivariate models: one with OCT parameters (model 1) and the other without OCT parameters (model 2). According to model 1, average RNFLT was the ultimate factor associated with the rate of MD progression.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Bambo et al . [ 18 ] compared the cp-RNFL and the macular GCIPL in glaucoma patients at different disease stages in a single OCT device (Cirrus HD OCT) and concluded that the inner macular parameters performed as well as cp-RNFL measurements in patients with different stages of glaucoma. However, in this study, the AUC was not calculated, and the discriminating ability of various parameters was evaluated on the basis of the difference in the mean values of the parameters in early, moderate, and advanced glaucoma.…”
Section: Discussionmentioning
confidence: 99%